Analisis Nilai-Nilai Pendidikan Karakter dalam Petuah Bijak dan Kisah Inspiratif Ulama Salaf dan Nusantara - Supriyanto, Agus (Educreative : Jurnal Pendidikan Kreativitas Anak, 2020)
Character education is a term that is increasingly gaining recognition from Indonesian society today. Character education is an attempt to educate children to be able to make wise decisions and practice them in their daily lives, so that they can make a positive contribution to their environment. Another definition is that character education is a process of transforming the values of life to be developed in the person's life behavior. Wise Advice and Inspirational Stories of Salaf and Archipelago Ulemas are those that contain a fragment of a story or behavior on how to educate students or in the daily life of Salaf and Nusantara scholars. Salaf and Nusantara scholars here which is one of the great scholars in the archipelago.